Chitosan complexed carboxymethylated iota-carrageenan oral insulin particles: Stability, permeability and in vivo evaluation - Sahoo, Pratyusa; Leong, Kok Hoong; Nyamathulla, Shaik; Onuki, Yoshinori; Takayama, Kozo; Chung, Lip Yong (Elsevier, 2019)
We previously reported that insulin-entrapped chitosan complexed carboxymethylated iota-carrageenan (CS/CMCi) particles exhibit pH-responsive swelling behavior. However, the particles’ stability in the enzymatic gastrointestinal environment, their drug permeability mechanism, and related in vivo studies have not been discussed to date. In this study, we investigated the stability, muco-adhesiveness, transport mechanism and in vivo assessment of the particles. The particles retained their bioactivity and displayed a generally stable behavior in the simulated enzymatic environment of the gastrointestinal tract with high muco-adhesiveness (79.1 ± 4.3%). The results of cellular membrane permeability experiments further suggested that insulin from the insulin-entrapped particles was transported across the Caco-2 cell monolayers mainly via the paracellular pathway. This activity was inferred by the trans-epithelial electrical resistance (TEER) and the apparent permeability coefficient (Papp) of the insulin-entrapped particles (22-fold greater than control insulin solution), suggesting that the opening of tight junctions (TJs) of Caco-2 cells was involved in the process. The particles did not exhibit significant cytotoxicity at 0.5–10.0 mg/mL based on 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium, inner salts (MTS) and lactate dehydrogenase (LDH) assays. Additionally, an in vivo study with diabetic Sprague Dawley (SD) rats revealed an extended blood glucose-lowering effect for up to 36 h (Cmax: 175.1 ± 23.7 mIU/L, Tmax: 5 h, AUC: 1789.4 ± 158.6). The estimated bioavailability of insulin from CS/CMCi particles in humans was 44.7–46.9%, which may be increased three fold compared with rats. Thus, the above results support the effectiveness of chitosan-complexed carboxymethylated iota-carrageenan particles as an oral insulin delivery system for extended glycemic control in basal insulin therapy. © 2019 Elsevier Ltd